The 2016 Mw 6.5 Pidie Jaya, Aceh, North Sumatra, Earthquake : reactivation of an unidentified sinistral fault in a region of distributed deformation - Muzli, Muzli (2019)
On 6 December 2016, an Mw 6.5 earthquake occurred in Pidie Jaya, Aceh, about 30 km to the north of the Sumatran fault (SF) that killed more than 100 people and destroyed ∼3000 buildings. Mainshock focal mechanism inversions using regional Agency for Meteorology, Climatology, and Geophysics of Indonesia (BMKG) broadband data and teleseismic waveform data all indicate a strike-slip event with a centroid depth of 11-15 km. The observed macrointensity data show that most of the damaged buildings are distributed along the coast, approximately perpendicular to the ruptured fault strike instead of parallel with it. The strong shaking and damage sites are primarily located on the coastal sedimentary soils, highlighting the importance of site conditions in determining risk. We used one-month data recorded by nine temporal broadband stations to locate aftershocks with gridsearch and double-difference algorithms, thereby resolving a linear trend of seismicity aligned in a northeast-southwest direction. The refined aftershock locations indicate a leftlateral rupture that is in agreement with the preliminary finite-fault slip inversion as well as geomorphic signatures of local geological structure. Using a well-located ML 4.2 aftershock for path calibration, we relocated the mainshock epicenter with regional P-wave arrivals. The refined epicenter falls within the cloud of the well-located aftershocks, whereas locations from the global and regional catalogs are located 10-20 km away. Aftershock focal mechanisms determined by the first motion reveal similar solutions as the mainshock. This earthquake sequence ruptured a previously unidentified fault that is either located at the west of the fault that produced the 1967 Mw 6.1 earthquake sequence or is actually at the same fault. The Pidie Jaya earthquake and other off-SF events suggest strong distributed crustal deformation in Aceh, highlighting the need for better understanding of active faulting and seismic hazard in this region.